Codzienność słyszących dzieci niesłyszących rodziców - Możdżyńska, Marzena (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In the context of reflections on the everyday life as an educational challenge, problems faced by the children of deaf parents will be presented. Their functioning appears to be completely different than this of their peers because of the disability of their parents who belong to a specific, not autonomous group with low self-esteem, who often experience frustration as a sign of lack of understanding and contact with the environment. The lack of natural communication in home is limiting to a great extent the development of linguistic efficiency of these children, as well as the capability of their social adaptation. Experiencing a specific family situation daily provokes in them a strong sense of belonging to two different environments, they identify both with the community of deaf as well as with normally hearing people. Already as a couple year old children they can act as mediators and interpreters of deaf parents. Is it not however a role too bothersome for them?
Keywords: CODA; dwukulturowość; dzieci; dzieci niesłyszących rodziców; język migowy; niepełnosprawność rodziców